1981
DOI: 10.1007/bf00264970
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation in maize plants regenerated during tissue culture selection

Abstract: Plants resistant to Helminthosporium maydis race T were obtained following selection for H. maydis pathotoxin resistance in tissue cultures of susceptible, Texas male-sterile (T) cytoplasm maize. The selected lines transmitted H. maydis resistance to their sexual progeny as an extranuclear trait. Of 167 resistant, regenerated plants, 97 were male fertile and 70 were classified male sterile for reasons that included abnormal plant, tassel, anther or pollen development. No progeny were obtained from these male-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

1984
1984
2004
2004

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(30 citation statements)
references
References 16 publications
2
26
2
Order By: Relevance
“…Third, both in our evolutionary and in vitro studies we noted that most of the structural alterations of the Brassica mitochondrial genome occur at specific sites via recombination across short repeated elements. Although a number of studies have already demonstrated an increased plasticity of plant mtDNA in response to tissue culture manipulations [ 17,7,39,41,50,21,4] it is still uncertain as to whether these 'culture-induced' alterations occur systematically in all higher-plant species or whether they reflect particular culture conditions such as culture age [34] or the in vitro technique employed [23]. A study of in vitro mtDNA alterations of maize [7] has also shown that the occurrence of specific types of rearrangements (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Third, both in our evolutionary and in vitro studies we noted that most of the structural alterations of the Brassica mitochondrial genome occur at specific sites via recombination across short repeated elements. Although a number of studies have already demonstrated an increased plasticity of plant mtDNA in response to tissue culture manipulations [ 17,7,39,41,50,21,4] it is still uncertain as to whether these 'culture-induced' alterations occur systematically in all higher-plant species or whether they reflect particular culture conditions such as culture age [34] or the in vitro technique employed [23]. A study of in vitro mtDNA alterations of maize [7] has also shown that the occurrence of specific types of rearrangements (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The maize urf13 gene is located upstream of a conserved mitochondrial gene termed orf221, which encodes a membranebound protein (Prioli et al, 1993), now identified as ATP4 (Heazlewood et al, 2003). Critical confirmation that urf13 causes pollen disruption came from characterizing mitochondrial genomes in fertile revertants that arose from cell culture (Gengenbach et al, 1981), in which were detected deletions that disrupted the urf13 gene (Umbeck and Gengenbach, 1983;Abbott and Fauron, 1986;Rottmann et al, 1987). A particularly important revertant was described by Wise et al (1987), who observed that a 5-bp insertion in urf13, causing a frame shift and a premature stop codon, was sufficient to confer fertility.…”
Section: Complex Mitochondrial Loci Associated With Cms the Multiply mentioning
confidence: 99%
“…Concurrently, a map-based approach took advantage of the male-fertile, toxin-insensitive mutants described above. In 19 of 20 such mutants, a 6.7-kb XhoI mitochondrial DNA restriction fragment was altered due to a partial deletion (Gengenbach et al, 1981;Kemble et al, 1982;Umbeck and Gengenbach, 1983;Fauron et al, 1987). The remaining male-fertile mutant, T-4, retained the 6.7-kb XhoI fragment.…”
Section: Disease Susceptibility and Male Sterilitymentioning
confidence: 99%